SINERGITAS KEMITRAAN ANTARA POLRI DENGAN PECALANG DALAM MENJAGA KEAMANAN DESA PAKRAMAN - Ni Made Liana Dewi (Fakultas Hukum Universitas Dwijendra, 2018)
ABSTRACT The beauty and hospitality of Bali with its various cultural and social uniqueness has been too often discussed. The island of Bali, which is called the Thousand Temple Island, has been famous throughout the world since before. Bali has become a symbol of tourism from Indonesia with various problems that may be faced. Community security and order building is the authority of the police. The social construction of Balinese people in maintaining public order and security still exists and is maintained from the past until now. Judging from the outline, there are threats that can disrupt the security situation in Bali are as follows: (a) Threats of narcotics crimes, (b) Threats of terrorism crimes (c) Threats of corruption habits, (d) Uncontrolled threat of population migration to Bali. In addition to these threats, Bali still has conventional threats that are always difficult to solve until now. What is meant is uncontrolled population growth. The arrival of immigrants from all over Indonesia from outside Bali is not wrong, but the problem is the density of the Balinese population who cannot be controlled and exceed the tolerance limit. The result is clearly felt today, the percentage of crime has increased sharply, snatching, muggings, pratima theft, rape and murder have become commonplace news in Bali.This thesis is a normative legal research by applying a historical approach, conceptual approach and legislation approach in analyzing the problems mentioned above. In addition, the sources of primary, secondary and tertiary legal materials collected by library techniques and document studies were processed and analyzed using qualitative descriptive methods. The theories used to dissect these problems are theories of authority, transformation theory, community engineering theory and structural functional theory . Keywords : Pecalang, Synergy, Police